Metodologia para definição de layout de praça de produção de carvão vegetal - Zola, Fernanda Cavicchioli (2020)
Charcoal is the foremost important material to substitute coal in the steel industry. So far, no study has been done to assist decision-makers in defining the technology used and the layout in the charcoal industry. In this study, a metodology is presented that helps the decison-maker to choose since the type of carbonization klin to the allocation of these resources in the production area in order to determine the best layout according to decision-making knowledge and needs. The facility layout problem (FLP) tends not to be used by less automated industries, such as charcoal, due to lack of knowledge of the methods. The iterative program helps the decision-making to use the method without the need of technical knowledge. For this, the multicriteria decision making method (MCDM) was used to select the carbonization kiln and the layout. To solve this problem with the influence of the decision making, we used the Analytical Hierarchy Process (AHP) method to evaluate the weight of the criteria in the kiln selection and, in order to allow the decision maker to analyze both quantitative and qualitative criteria, we opted for the Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in choosing the ideal solution. Additionally, the program performs the sizing of machines and spaces and for selection of the layout it was used the Layout Systematic Planning Method (SLP), where the decision making generates three scenarios that are ranked using the AHP method in the weighting of the criteria and the Fuzzy TOPSIS method as a tool to choose of the best scenario. Combined with the AHP method, the TOPSIS fuzzy method proved to be very efficient both in helping to choose the carbonization kiln and in deciding the layout, since it allowed industry conditions to be considered. Conclusively, the method generates different results for each case and each decision-maker, showing itself to be a successful tool for the charcoal industry, since it selects the most suitable kiln and its layout, thus boosting the production of renewable energy.